2019
DOI: 10.1186/s12913-019-4299-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the quality of seasonal malaria chemoprevention provided by community health Workers in Boulsa health district, Burkina Faso

Abstract: Background Since 2014, the Burkina Faso government has made Seasonal Malaria Chemoprevention (SMC) a priority in its strategic plan to fight against malaria among children aged from 3 to 59 months. Very few studies have examined the care provided by community health workers in the framework of this strategy. The purpose of this study was to evaluate the level of quality of care provided by the latter. Methods This was a mixed study. The quantitative component consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
4
0
3
Order By: Relevance
“…These results are nonetheless consistent with another study on community health workers' performance conducted in Burkina Faso, Nigeria, and Uganda, where 98% of the tasks were mastered by respondents [15]. They are also consistent with those of a recent observational study conducted in the same context with 14 CBDs, which concluded that they "deliver acceptable quality of care" [16]. Studies have also shown that SMC has contributed significantly to reducing both malaria transmission and the biological prevalence of anaemia in children under five [3].…”
Section: Discussionsupporting
confidence: 90%
“…These results are nonetheless consistent with another study on community health workers' performance conducted in Burkina Faso, Nigeria, and Uganda, where 98% of the tasks were mastered by respondents [15]. They are also consistent with those of a recent observational study conducted in the same context with 14 CBDs, which concluded that they "deliver acceptable quality of care" [16]. Studies have also shown that SMC has contributed significantly to reducing both malaria transmission and the biological prevalence of anaemia in children under five [3].…”
Section: Discussionsupporting
confidence: 90%
“…One of the fears of integrating interventions or health service delivery is a compromise on quality of delivery following integration. This has been adduced to low adherence to quality guidelines due to limited time or extra workload [ 31 ]. However it has been established that CHWs can deliver quality services with adequate supervision, motivation and supplies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These obstacles include a lack of stable funding, retention challenges, inadequate training and supervision, and parallel and concurrent interventions. Our study and another [44] carried out on SMC in Burkina Faso showed that the overload of work of community distributors contributed to decreasing their performance in the effective administration of drugs and the transmission of information to caregivers. Therefore, by grafting a new intervention such as SMC into a "faulty" system without providing systemic solutions to existing problems, there is a risk of jeopardizing the sustainability of innovations or the quality of other existing interventions.…”
Section: The Verticality the Smc Campaign: Structural Challengesmentioning
confidence: 62%